2008
DOI: 10.1007/s00705-007-0015-4
|View full text |Cite
|
Sign up to set email alerts
|

New clade of betanodaviruses detected in wild and farmed cod (Gadus morhua) in Norway

Abstract: Betanodaviruses have been isolated and detected in both farmed and wild fish species worldwide. They are classified in five clusters, and all are connected to mortalities in farmed fish. The clusters do not represent specific geographical areas or host species, but one cluster, barfin flounder nervous necrosis virus (BFNNV), is mainly associated with cold water fish species. This study presents the first species-specific clade within the BFNNV cluster. This clade consists of six isolates from wild and farmed A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…The detection of nodavirus in Tunisia occurred several years ago in farmed sea bass and sea bream [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In this study, the causative agent was detected from feral fish species for the first time.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The detection of nodavirus in Tunisia occurred several years ago in farmed sea bass and sea bream [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In this study, the causative agent was detected from feral fish species for the first time.…”
Section: Discussionmentioning
confidence: 86%
“…RNA1 encodes an RNA-dependent RNA polymerase, whereas RNA2 encodes the coat protein gene [6]. At least five genogroups are recognized: red-spotted grouper nervous necrosis virus (RGNNV), striped jack nervous necrosis virus (SJNNV), barfin flounder nervous necrosis virus (BFNNV), tiger puffer nervous necrosis virus (TPNNV) and turbot nervous necrosis virus (TNNV) [7][8][9]. In the Mediterranean, Nodaviruses have been isolated from a number of wild and farmed fish species, including European sea bass Dicentrarchus labrax (L.), for which VNN is a major constraint in hatcheries [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, phylogenetic analyses of isolates originating from halibut and cod indicate a high degree of similarity. They cluster as closely related groups in the BFNNV clade (Nylund et al 2008). Moreover, a NNV strain isolated from commercially farmed cod has previously been identified belonging to the halibut cluster (A. Nylund unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Recently NNV has been detected and VNN diagnosed in several commercial cod farms on the west coast and northern part of Norway, and the virus has also been detected in wild Atlantic cod (Nylund et al 2008). Elsewhere, Johnson et al (2002) have reported NNV in Atlantic cod in Canada, and Starkey et al (2001) reported NNV in Atlantic cod hatched from wild stock from the Irish Sea.…”
Section: Introductionmentioning
confidence: 97%
“…Clustering of isolates within genotypes has also been described after phylogenetic analysis of SJNNV isolates from the Iberian Peninsula, where 2 distinct clusters designated as IVa and IVb were reported (Cutrín et al 2007). Nylund et al (2008) identified 3 clusters, which are designated as Atlantic halibut nervous necrosis virus (AHNNV), cod nervous necrosis virus (GMNNV) and ACNNV, within the BFNNV genotype after phylogenetic analysis of betanodavirus isolates from Norway. The 3 BFNNV clusters are very similar to the IIa, IIb and IIc clusters within the BFNNV genotype described by Thiéry et al (2004), and adopted in Fig.…”
mentioning
confidence: 99%